Cover Image. (18th November 2021) - Henderson, Aria R.; Ilan, Isabelle S.; Lee, Esak
Abstract : The cover image is based on the Original Article A bioengineered lymphatic vessel model for studying lymphatic endothelial cell‐cell junction and barrier function by Esak Lee et al., https://doi.org/10.1111/micc.12730 .